RANCANG BANGUN PERANGKAT KERAS SISTEM SMART LAMPU PENERANGAN JALAN UMUM BERBASIS INTERNET OF THINGS GUNA MENDUKUNG IMPLEMENTASI SMART CITY - Dharma Dutaluhur Artha Lesmana; I Made Arsa Suyadnya; I Wayan Shandyasa (Program Studi Teknik Elektro UNUD, 2023)
Public Street Lighting (PJU) is a lighting system designed to provide street lighting at night with the aim of increasing comfort for pedestrians and motorists passing through. However, the obstacles faced regarding PJU lights at this time are that when carrying out monitoring and control officers are still checking and visiting the location of every whereabouts of PJU lights. So that to make it easier for officers to manage PJU lights in this study, they will conduct discussions related to the design and development of hardware that is applied to PJU lights. The methods used in the development of this system are design, development, and testing. To build hardware using components such as ESP32 as a microcontroller, PZEM004Tv30 sensor, DHT22 sensor, IC RTC DS3231, Relay 30 A, IC LM2596 5V, IC AMS1117 3.3V, GSM SIM808 Module and LDR sensor, while for implementing the protocol using the MQTT protocol and Antares as the MQTT platform. The results of tests carried out on each circuit block in hardware such as the DHT22 sensor have an accuracy range of 0.1 – 0.2, the PZEM004Tv30 sensor has an accuracy range of 0.3 – 0.5, Regulator IC LM2596 5V and AMS1117 3.3V each has an appropriate output voltage of 5V and 3.3V, and the CH340C IC Driver IC can work and read properly.